STIMULASI INTERVENSI DETEKSI DINI TUMBUH KEMBANG (SIDTK) DI TK NURUL HIKMAH NAGARI KASANG BATANG ANAI PADANG PARIAMAN - Imanniyah Wati (Jurnal Pengabdian Barelang, 2020)
This community service activity aims to foster children's growth and development comprehensively and with quality through stimulation, detection and early intervention activities for growth and developmental deviations in the first 5 years of life. SIDTK is conducted in the Pasar Usang Puskesmas area, especially in Nurul Hikmah Kanagarian Kasang Kindergarten. This dedication activity is carried out by detecting the growth and development of children in Nurul Hikmah Kindergarten by jumping directly on the children to get immediate results of examinations such as weight, height, head circumference, and mental emotional problems as well as delays in communication, namely language and speech. Achieving these goals is done through training with lecture, question and answer and giving intervention methods. As for suggestions that can be submitted from the results of community service, for kindergarten teachers are expected to always seek SDITK activities for their students. Health practitioners are expected to be able to help kindergarten teachers in conducting SIDTK regularly. For LP2M through STIKes Mercubaktijaya Padang it should always entice similar programs to continue to be implemented and developed.